(3TQM GdJLQjOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO HGbQ Hf eMeO eSjHM GdNWjHs)
(3ChdgG (B:s
(3GdebUO GdKGdK aj EKHGJ GdUGfY JYGdi hUaGJg hBKGQg hajg aUhd(B: (3GdChd aj hLhOg GdehLhO Ef cGf hGLHG hEdG GSJdReg dGSJMGdI GdOhQ hGdJSdSd(B...s
(3BNQgG (B:s
... (3Ke Efg aQV caGjI dG aQV Yjf aEPG bGe Hg bhe SbW Yf GdBNQjf hEPG (B.. (3cd WGFaI Cfg de Jbe Hg GdBgQ CKe Gdcd HJQcg gPG eG JjSQ dfG ef TQM JLQjO GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3GdPQjYI (B18 - 40 ( 668)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds